Toward Sustainable Cost Accounting: Drivers, Barriers, and Institutional Dynamics - Ibrahim, Fifi Nurafifah; Gangodawilage, Damith (Yayasan Sinergi Kawula Muda, 2024)
This narrative review explores the evolving landscape of sustainable cost accounting by analyzing key economic, socio-cultural, and regulatory drivers that shape its adoption. The study aims to synthesize empirical findings and theoretical insights to understand the systemic enablers and barriers influencing transformation efforts. Methodologically, the review follows a thematic synthesis of peer-reviewed literature, examining how innovations in technology, institutional frameworks, and organizational dynamics interact with sustainability objectives. Findings reveal that integrating environmental and social externalities into cost accounting enhances operational efficiency, financial transparency, and stakeholder trust. Digital tools such as cloud analytics and real-time reporting are identified as enablers that reduce operational costs and improve decision-making accuracy. However, conceptual fragmentation, resistance to change, and lack of methodological standardization hinder widespread implementation. The discussion underscores the role of regulatory institutions, global reporting standards, and stakeholder expectations in facilitating systemic transformation. Investment in digital infrastructure and cross-sectoral partnerships is recommended to overcome institutional inertia and scale implementation. Moreover, emerging evidence supports the need for integrated reporting models and predictive technologies to measure long-term sustainability impacts. In conclusion, transitioning to sustainable cost accounting requires a multidimensional approach, combining technological innovation, institutional support, and cultural adaptation. This review provides a foundation for future research and policy aimed at achieving transparent, accountable, and sustainability-driven cost accounting practices.